Sucessão no sistema Sicredi: um diagnóstico dos fatores impeditivos e critérios importantes para a implementação do plano de sucessão - Meinen, Alceu Ruppenthal (Universidade do Vale do Rio dos Sinos, 2019)
Financial Cooperativism has increasingly become a leading player in the national financial market, due to its business model, that despite being secular, is more current than ever before. Anyways, this protagonism has not been seen in terms of leadership succession. Focused on that, the present study aims to identify, through the cooperatives associated to the South-Southeast Central of Sicredi what are the constraining factors for implementing succession plans to the positions of Board President and Executive Directors, and comprehend what are the reasons that lead to the non-implementation of a standardized succession plan, which can impact the continuity of the cooperative business. However, the literature shows that the difficulty for the implementation of a succession plan is not restricted to Sicredi. Therefore, in a qualitative-descriptive manner, through a case study, executives from the cooperatives were interviewed. After the analysis of the content, it was possible to verify which are the factors that make the succession process difficult and the hinderings for the implementation of a systemic model. As the main factor I would mention that the lack of interest by leaders in the implementation of a succession plan is due to the status of the position they stand in their regions and communities. Thus, based on this study, it was possible to conclude that for the success of a succession plan implementation, Sicredi should watch out for these key factors that hinder such process and what are the criteria that can be observed in the construction of a succession plan for further implementation.
Keywords: Sucessão; Matriz de talentos; Governança e cooperativas financeiras; Succession; Talent matrix; Governance and financial cooperatives; ACCNPQ::Ciências Sociais Aplicadas::Administração